1999
DOI: 10.1001/jama.281.7.621
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Missed Cases of Abusive Head Trauma

Abstract: Although diagnosing head trauma can be difficult in the absence of a history, it is important to consider inflicted head trauma in infants and young children presenting with nonspecific clinical signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
566
4
10

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 972 publications
(619 citation statements)
references
References 26 publications
19
566
4
10
Order By: Relevance
“…[67][68][69][70] The prevalence of abuse in young children with head injury was also high, ranging from 14% to 70% depending on the age of the child, the type and severity of head injury and the measurement of physical abuse. [71][72][73][74][75][76] …”
Section: Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[67][68][69][70] The prevalence of abuse in young children with head injury was also high, ranging from 14% to 70% depending on the age of the child, the type and severity of head injury and the measurement of physical abuse. [71][72][73][74][75][76] …”
Section: Review Resultsmentioning
confidence: 99%
“…Jenny, USA, 1999 (head) 74 Brown, USA, 2003 (head) 72 Ziegler, Australia, 2005 (fracture) 86 Scherl, USA, 2000 (fracture) 83 Oral, USA, 2003 (fracture) 82 Carty, UK, 2002 (fracture) 85 Kumar, UK,1984 (burns) 81 Clark, USA, 1997 (burns) 80 Hoskote depending on the type and severity of injury, the threshold for referral, the criteria for confirmation of abuse and the accuracy of clinicians who decided which children to refer. All of the included studies were based on specific injury groups that would be classified post hoc, after investigation, and which are therefore likely to be based on highly selected populations, at higher risk of abuse than the average injured child attending A&E. 65,70,87 The included studies suggest some consistency in the risk of abuse for burns 80,81 but not for other types of injury.…”
Section: Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 25 years, research has repeatedly highlighted missed opportunities to evaluate and diagnose abuse in young, injured children, resulting in children suffering from undiagnosed injuries as well as ongoing abuse. [36][37][38][39][40][41][42][43] Research has also revealed that racial and socioeconomic status (SES)-based biases influence decision-making regarding child abuse evaluations and diagnoses. 17,31,35,44,45 A single institution study of unwitnessed TBI in infants showed that implementation of a guideline for universal occult fracture evaluation in this population can eliminate racial and SES-based disparities and might increase the detection of abuse.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the diagnosis of child abuse is missed by unsuspecting physicians and that diagnostic specificity is improved when physicians are adequately trained to recognize both inflicted injuries and medical mimickers of abuse. 19,20 It is concerning that physicians in Alabama, and likely throughout the country, are asked to evaluate and care for patients with such potentially important diagnoses without adequate training, experience, or professional support. Considering that child maltreatment is more prevalent than cancer and just as fatal, it should warrant more attention during residency training than the time spent on recognizing less commonly occurring diseases.…”
Section: Physicians In Practicementioning
confidence: 99%